Lipopolysaccharide induces acute lung injury and alveolar haemorrhage in association with the cytokine storm, coagulopathy and AT1R/JAK/STAT augmentation in a rat model that mimics moderate and severe Covid‐19 pathology. (9th February 2022) - Al‐Ani, Bahjat; ShamsEldeen, Asmaa M.; Kamar, Samaa S.; Haidara, Mohamed A.; Al‐Hashem, Fahaid; Alshahrani, Mohammad Y.; Al‐Hakami, Ahmed M.; Kader, Dina H. Abdel; Maarouf, Amro
Abstract: Progress in the study of Covid‐19 disease in rodents has been hampered by the lack of angiotensin‐converting enzyme 2 (ACE2; virus entry route to the target cell ) affinities for the virus spike proteins across species. Therefore, we sought to determine whether a modified protocol of lipopolysaccharide (LPS)‐induced acute respiratory distress syndrome in rats can mimic both cell signalling pathways as well as severe disease phenotypes of Covid‐19 disease. Rats were injected via intratracheal (IT) instillation with either 15 mg/kg of LPS (model group) or saline (control group) before being killed after 3 days. A severe acute respiratory syndrome (SARS)‐like effect was observed in the model group as demonstrated by the development of a "cytokine storm" (>2.7 fold increase in blood levels of IL‐6, IL‐17A, GM‐CSF, and TNF‐α), high blood ferritin, demonstrable coagulopathy, including elevated D‐dimer (approximately 10‐fold increase), PAI‐1, PT, and APTT ( p < 0.0001). In addition, LPS increased the expression of lung angiotensin II type I receptor (AT1R)‐JAK‐STAT axis (>4 fold increase). Chest imaging revealed bilateral small patchy opacities of the lungs. Severe lung injury was noted by the presence of both, alveolar collapse and haemorrhage, desquamation of epithelial cells in the airway lumen, infiltration of inflammatory cells (CD45+ leukocytes), widespread thickening of the interalveolar septa, and ultrastructural alterations similar to Covid‐19. Thus, these findings demonstrate that IT injection of 15 mg/kg LPS into rats, induced an AT1R/JAK/STAT‐mediated cytokine storm with resultant pneumonia and coagulopathy that was commensurate with moderate and severe Covid‐19 disease noted in humans.